Competition, Conflict and Change of Mind: A Role of GABAergic Inhibition in the Primary Motor Cortex - Ribot, Bastien; de Rugy, Aymar; Langbour, Nicolas; Duron, Anne; Goillandeau, Michel; Michelet, Thomas (Frontiers in Human Neuroscience, 2022)
Deciding between different voluntary movements implies a continuous control of the competition between potential actions. Many theories postulate a leading role of prefrontal cortices in this executive function, but strong evidence exists that a motor region like the primary motor cortex (M1) is also involved, possibly via inhibitory mechanisms. This was already shown during the pre-movement decision period, but not after movement initiation. Here we designed a new task compatible with the dynamics of post-initiation control to study the silent period (SP) duration, a pause in electromyographic activity after single-pulse transcranial magnetic stimulation that reflects inhibitory mechanisms. A careful analysis of the SP during the ongoing movement indicates a gradual increase in inhibitory mechanisms with the level of competition, consistent with an increase in mutual inhibition between alternative movement options. However, we also observed a decreased SP duration for high-competition trials associated with change-of-mind inflections in their trajectories. Our results suggest a new post-initiation adaptive process that consists in a transient reduction of GABAergic inhibition within M1 for highly conflicting situations. We propose that this reduced inhibition softens the competition between concurrent motor options, thereby favoring response vacillation, an adaptive strategy that proved successful at improving behavioral performance.